SCIENCES OF ROGER BACON'S OPUS MAIUS ([S.l.])
1 online resource
Keywords: Through an examination of the Opus maius, Roger Bacon's great scientific work of 1267, this book offers insight into Bacon's understanding of the role of science in society and the study and practice of science in the later Middle Ages.Written at the request of Pope Clement IV (d. 1268), the Opus maius contains English Franciscan and polymath Roger Bacon's plans for educational and ecclesiastical reform through the study of arts and sciences, which Bacon saw as having been neglected in the curricula of the major European universities. In writing the Opus maius, Bacon wanted to demonstrate that not only were the sciences a solid foundation for learning theology, but they could also improve society and help mankind attain salvation. This volume contains nine essays on the sciences Bacon thought were most important in this scheme, including optics, mathematics, astronomy, alchemy, medicine, and experimental science. Each provides a focused examination of the individual sciences, demonstrating how Bacon understood and practised them, as well as how he envisioned they would fit together into his larger programme of scientific reform.This thought-provoking collection will be a valuable resource to historians of science, medicine, and philosophy, as well as those in medieval and premodern studies.